Preparation Of Acrylate Base Graphene And Graphene Oxide (Go) Nanocomposite Via Physical Blending As Pour Point Depressants (Ppd) - Osman, Maizatul Akmaliah (Universiti Sains Malaysia, 2017)
The nanoparticle material such as Graphene and Graphene Oxide can be applied as an additive in Emulsified Pour Point Depressant since it can be improvise the properties of PPD. By using solution intercalation method as physical blending to produce Graphene and Graphene Oxide well disperse in Emulsified Pour Point Depressant. Graphene dissolved in water, and then the mixture has been sonicate for 30 minutes. While, Graphene Oxide was pour in water, ethylene glycol and MWV, and then stir for two minutes. After that, the oil basecontaining acrylate polymer was pour into water base mixture, then it stirred for 1 hour. Finally, the mixture was sonicate in preparation sample around 3 minutes to get better dispersion between nanoparticles with emulsified PPD. Thus, the good dispersion are held together by the Van der Waals interaction between nanoparticles with acrylate polymer. Fourier Transform Infra-Red (FTIR), Differential Scanning Calorimetry (DSC), Scanning Electron Microscopy (SEM), Thermogravimetric analysis (TGA), X-Ray Diffraction (XRD), Particle Size Distribution, Zeta Potential, Aging Test, Freeze Thaw Test, ASTM D97 were conduct to characterize the sample.Using FTIR result, hydroxyl group was identified in the emulsion sample that justified with the presence of water and ethylene glycol. In addition, the ester group, carboxylic group and hydroxyl group shows the presence of nanoparticles material in emulsion. It can be simplified for DSC thermogram, all Emulsified Nano-hybrid PPD had better cold flow properties compared to Normal Emulsified PPD (without nanoparticles). In TGA, all Emulsified Nano-hybrid PPD decomposed completely at 480°C. Based on XRD results, Emulsified Nano-hybrid PPD shows the highest crystallinity compared to Normal Emulsified PPD. The particle size measurement proved that, cycle per week for aging increased and freeze thaw test also increase the particle size distribution and zeta potential changes, since the colloidal of particles are not in stable when nanoparticles doped in emulsion. Furthermore, using the pour point reduction test, Emulsified Nano-hybrid PPD with optimum dosing (1500ppm) is the most effective sample act as PPD since it show the most pour point reduction containing 16°C compared to other samples.